Development of tool use in New Caledonian crows: inherited action patterns and social influences - Kenward, B; Rutz, C; Weir, A; Kacelnik, A (2006)
New Caledonian crows, Corvus moneduloides, are the most advanced avian tool makers and tool users. We previously reported that captive-bred isolated New Caledonian crows spontaneously use twig tools and cut tools out of Pandanus spp. tree leaves, an activity possibly under cultural influence in the wild. However, what aspects of these behaviours are inherited and how they interact with individual and social experience remained unknown. To examine the interaction between inherited traits, individual learning and social transmission, we observed the ontogeny of twig tool use in hand-reared juveniles. Successful food retrieval was preceded by stereotyped object manipulation action patterns that resembled components of the mature behaviour, demonstrating that tool-oriented behaviours in this species are an evolved specialization. However, there was also an effect of social learning: juveniles that had received demonstrations of twig tool use by their human foster parent showed higher levels of handling and insertion of twigs than did their naïve counterparts; a choice experiment showed that they preferred to handle objects that they had seen being manipulated by their human foster parent. Our observations are consistent with the hypothesis that individual learning, cultural transmission and creative problem solving all contribute to the acquisition of the tool-oriented behaviours in the wild, but inherited species-typical action patterns have a greater role than has been recognized. © 2006 The Association for the Study of Animal Behaviour.